The role of akidah akhlak teacher in embedding character of polite and decent language for elementary students - Kartika Dwi Astuti; Muqowin Muqowim (Prodi PGMI IAIN Salatiga, 2021)
Indonesia well known as a nation that Cary on the head of polite and decent caharcter, especially in the use of language. Recently many cases were found that students are impolitely speaking, even bullying teachers. For this reason that embedding character of polite and decent language for early childhood is necessary. This study aims to identify the role of Akidah Akhlak teacher in embedding the character of polite and decent language for students’ year 1 at MIN 1 Bantul. The subject of this study is Akidah Akhlak, teacher of year 1 in MIN 1 Bantul. This study used a qualitative method with a descriptive approach. Data gathered through interviews and analyzed using qualitative analysis. Triangulate technic is used to validate the data and to recheck the result of the interview. This study showed that the role of Akidah Akhlak teacher is to give comprehension, become an example, and a role-model, doing observation and evaluation with the support from school stakeholders in embeeding polite and decent language through daily activities.